Asset liquidity and venture capital investment - Nguyen, Giang; Vo, Vinh (Journal of corporate finance (Amsterdam, Netherlands), 2021)
We examine the relationship between asset market liquidity and venture capital (VC) investment and find that it is inverted U-shaped. Asset liquidity and VC investment are positively related for low levels of asset liquidity but negatively related for higher levels of asset liquidity. We also document evidence that VC firms with more industry experience invest more in a liquid asset market than those without industry experience or with significant experience in other industries. Portfolio companies obtained their first investment in a liquid asset market are less likely to exit successfully; however, given a successful exit, they prefer to exit through mergers and acquisitions rather than going public. •We examine the relationship between asset liquidity and venture capital (VC) investments•We find that the relationship is inverted U-shaped.•VCs with more industry experience invest more in a liquid asset market.•Portfolio companies received their first investment in a liquid asset market are unlikely to exit successfully.•Given a successful exit, portfolio companies prefer M&As rather than going public in a liquid asset market.